Performa Ayam Kampung Asli dan Ayam Kampung Unggul Balitbangtan Periode Starter yang Diberikan Tepung Maggot BSF - Utama, Duta Dhyas; Priyambodo, Danang; Rayani, Tera Fit; Sembada, Pria; Ayuningtyas, Gilang (Jurnal Agroekoteknologi dan Agribisnis, 2025)
BSF maggot meal has the potential as an alternative raw material for animal feed that is rich in animal protein, especially in the cultivation of local broiler chickens. AKA chickens and KUB chickens are local meat chickens that are widely cultivated in Indonesia. AKA chickens and KUB chickens are local meat chickens that are widely cultivated in Indonesia. The study aimed to examine the performance of AKA and KUB chickens during the starter period given feed containing 7,5% BSF maggot meal. The experimental design in this study used a completely randomized design (CRD). Maintenance or research was conducted for four weeks with observations on three thousand AKA (P1) and three thousand KUB (P2) chickens, each divided into two repetitive groups. The observed variables were the performance of local poultry performance of starter period chickens. The results showed that the provision of 7,5% BSF maggot meal in feed had a significant effect (P<0,05) on body weight, body weight gain, depletion rate and feed conversion of the starter period. Body weight fourth week in P1 was 181,11±0,62 and P2 was 157,97±0,75. Cumulative body weight gain in P1 was 149,12±0,78 and P2 was 130,32±0,31. The depletion rate of P1 was 10,20±0,28 and P2 was 24,08±0,04. Feed conversion of body weight of P1 was 2,69±0,01 and P2 was 3,10±0,01. Based on these parameters, the performance of AKA chickens was better when compared to the performance of KUB chickens. Providing feed containing maggot meal to local broiler chickens can produce good production performance during the starter period, and AKA chickens provide a better response compared to KUB chickens.